Designing a residential’s database management system: a case study of applying resource, event and agent (REA) approach - Zainol, Zaini; toha, siti noratika; azman, nur azlinda; paling, rajinah; abdullah, mardhiah (Springer Nature, 2022)
Nowadays, with more and more data is created every second, the dependency on reliable database management systems (DBMS) is so crucial. In the case of a residential college, students’ frequent changes every semester have made the process of keeping track of students’ data a daunting task. Hence, this paper is conducted to document the proposal of creating a DBMS for the administrative staff in a residential college to record and keep track of the student’s necessary information. The database is constructed using the resource, event, and agent (REA) approach, and following the software development life cycle (SDLC) implementation stages. Methods such as interviews, observation, and document review are used to gather information from relevant parties. As a result, a database is designed using Microsoft Access platform. Also, several benefits, limitations and recommendations are acknowledged for future improvement of the database.